Memahami Perilaku Kekerasan Penyidik Polri terhadap Tersangka pada Tahapan Pra-Adjudikasi (Studi Kajian Ilmu Hukum Normatif Dengan Pendekatan Psikologi Hukum Dalam Sistem Peradilan Pidana) - Ramlani Lina Sinaulan (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
On the development of law (rechtsbeoefening) both practical and theoretical, a scientist Law (academics and legal practitioners) often ignore the studies of the social aspects. In this case, a scientist Law (academics and legal practitioners) are trapped and confined on the nature of Legal Studies as a normative science. Thus, the development often collide in the level of practice of law in relation to the fulfillment of public sense of justice. In fact, the law enforcement authorities, especially police investigators, based on the pattern of education, obviously prefers cultural improvement of law and override the Legal Psychology. So, almost certainly, a police investigator in carrying out its duties and functions will never escape, in fact, are still stuck with the principle inquisatoir in examinations investigation.